From glosses to dictionaries the beginnings of lexicography - Benati, Chiara; Händl, Claudia (Cambridge Scholars Publishing, 2019)
This book presents--through a series of nine high quality essays by international scholars--the beginnings of the lexicographic tradition and the appearance of the first mono- and multilingual dictionaries in various language areas across the world, paying particular attention to their dependence on glosses and glossaries. The contributions analyze, on the basis of significant case studies, how dictionaries first emerged in a wide spectrum of cultures, ranging from Greek Antiquity to 9th-century Japan, from Medieval Britain to 15th-century Poland. In this way, the book highlights both similarit.